2015
DOI: 10.3174/ajnr.a4265
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Global and Regional Structural Networks and Subnetworks in Children with Localization-Related Epilepsy

Abstract: BACKGROUND AND PURPOSE:Structural connectivity has been thought to be a less sensitive measure of network changes relative to functional connectivity in children with localization-related epilepsy. The aims of this study were to investigate the structural networks in children with localization-related epilepsy and to assess the relation among structural connectivity, intelligence quotient, and clinical parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…Other investigators have also found particularly pronounced global connectivity disturbances in pediatric patients with frontal lobe epilepsy. Widjaja et al performed DTI analysis in children with nonlesional frontal lobe epilepsy, observing reduced structural connectivity in patients versus controls reflected by diminished network strength, clustering coefficient, path length, and global efficiency. This global network dysfunction may be related to widespread thinning of the neocortex also noted in this patient population .…”
Section: Global Connectivity Alterationsmentioning
confidence: 99%
“…Other investigators have also found particularly pronounced global connectivity disturbances in pediatric patients with frontal lobe epilepsy. Widjaja et al performed DTI analysis in children with nonlesional frontal lobe epilepsy, observing reduced structural connectivity in patients versus controls reflected by diminished network strength, clustering coefficient, path length, and global efficiency. This global network dysfunction may be related to widespread thinning of the neocortex also noted in this patient population .…”
Section: Global Connectivity Alterationsmentioning
confidence: 99%
“…Studies using diffusion-weighted imaging have identified 'disconnection syndromes' in schizophrenia (Stephan et al, 2009;Zalesky et al, 2011), depression (Bai et al, 2012), attention-deficit hyperactivity disorder (Cao et al, 2013), and epilepsy (Widjaja et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Here the focus of interest has been the impact of epilepsy and its treatment on brain development and understanding the relationship of abnormalities in brain structure with commonly occurring cognitive, academic, and behavioral comorbidities (Besseling et al, 2014; Bonilha et al, 2014; Braakman et al, 2014, 2015; Ibrahim et al, 2014; Widjaja et al, 2014a; Widjaja et al, 2015; Widjaja et al, 2014b). …”
Section: Introductionmentioning
confidence: 99%